Critical Factors Influencing ASIK Itilization: A Mixed-Methods Study of Health Worker Performance in Primary Health Centers - Mutiara Miftahul Jannah; Firdawati Firdawati; Rinang Mariko; Yuniar Lestari; Afdal Afdal; Eka Novita (Napande: Jurnal Bidan, 2026)
Background: ASIK is a key component of Indonesia’s health digital transformation for immunization recording and reporting. However, its implementation in Community Health Centers (Puskesmas) in Padang City faces challenges, including data discrepancies and suboptimal immunization coverage. This study examines factors associated with health workers’ performance in using ASIK and explores the underlying reasons for these challenges. Method: A mixed-methods study was conducted in five Puskesmas in Padang City. The quantitative phase included 127 health workers using a cross-sectional design, validated questionnaires, chi-square tests, and multivariate logistic regression. The qualitative phase involved in-depth interviews with 13 key informants and thematic analysis. Result: Quantitative analysis showed that motivation (p = 0.014), leadership (p = 0.018), and workload (p = 0.009) were significantly associated with performance, while knowledge was not (p = 0.602). In multivariate logistic regression, motivation was the dominant factor (Exp(B) = 0.254; 95% CI: 0.088–0.734; p = 0.011), indicating that health workers with poor motivation had approximately 74% lower odds of achieving good performance after controlling for leadership and workload. The final model explained 19.5% of performance variance (Nagelkerke R² = 0.195). Qualitative findings identified seven themes: professional responsibility-driven motivation, infrastructure limitations, application bugs, increased administrative workload, digital generation gaps, adaptive strategies, and the need for a single integrated application. Conclusion: Health workers’ performance in using ASIK was relatively good (79.5%) despite systemic barriers, mainly supported by intrinsic professional motivation. However, relying on individual resilience may be unsustainable. Improving ASIK requires addressing technical problems, reducing workload, bridging the digital divide, and strengthening health workers’ professional dedication.